Host specificity and species colouration mediate the regional decline of nocturnal moths in central European forests. Issue 6 (30th March 2021) - Roth, Nicolas; Hacker, Herrmann Heinrich; Heidrich, Lea; Friess, Nicolas; García‐Barros, Enrique; Habel, Jan Christian; Thorn, Simon; Müller, Jörg
Abstract : The high diversity of insects has limited the volume of long‐term community data with a high taxonomic resolution and considerable geographic replications, especially in forests. Therefore, trends and causes of changes are poorly understood. Here we analyse trends in species richness, abundance and biomass of nocturnal macro moths in three quantitative data sets collected over four decades in forests in southern Germany. Two local data sets, one from coppiced oak forests and one from high oak forests included 125K and 48K specimens from 559 and 532 species, respectively. A third regional data set, representing all forest types in the temperate zone of central Europe comprised 735K specimens from 848 species. Generalized additive mixed models revealed temporal declines in species richness (−38%), abundance (−53%) and biomass (−57%) at the regional scale. These were more pronounced in plant host specialists and in dark coloured species. In contrast, the local coppiced oak forests showed an increase, in species richness (+62%), while the high oak forests showed no clear trends. Left and right censoring as well as cross validation confirmed the robustness of the analyses, which led to four conclusions. First, the decline in insects appears in hyper diverse insect groups in forests and affects species richness, abundance and biomass. Second, the pronounced decline in host specialists suggests habitat loss as an important driver of the observed decline. Third, the more severe decline in dark species might be an indication of global warming as a potential driver. Fourth, the trends in coppiced oak forests indicate that maintaining complex and diverse forest ecosystems through active management may be a promising conservation strategy in order to counteract negative trends in biodiversity, alongside rewilding approaches.